EGG PRODUCTION AND EGG QUALITY TRAITS IN RAJASRI BIRDS REARED UNDER SCAVENGING AND OTHER SYSTEMS OF MANAGEMENT - S.QUDRATULLAH, V.CHINNI PREETAM, V. RAVINDER REDDY, SRINIVAS GURRAM AND (The Journal of Research, PJTSAU, 2019)
A study was conducted to evaluate the growth and production performance of Rajasri, a synthetic backyard bird during growing and laying period. The birds were reared under different systems of management and feeding regimens, ad lib feeding group (T1) reared under intensive system while 20% of ad lib (T2) and 40% of ad lib (T3) groups were reared under semi-intensive condition and T4 group was reared under scavenging at farmers backyard. The results revealed that the body weight gain was significantly (P<0.05) higher for T1 group (1085.62g) followed by T3, T2 and T4 groups respectively during growth phase (7-20 weeks). Whereas poorest FCR was recorded in T1 group (6.38) than T2 (3.32) and T3 (4.28) groups. Liveability was significantly (P<0.05) better with intensive system and least with scavenging system. The age at first egg and 50% egg production was significantly better in ad lib fed group (146.5d and 165.75d) followed by scavenging group (T4) and much inferior with feed restricted groups (T2 > T3). The mean per cent hen day egg production over 10 laying periods was significantly better with ad lib. group (56.83%) and least with 20 and 40% ad lib (22.10 and 29.23%). Scavenging at farmer’s backyard resulted in 37.81%. The egg weight was significantly inferior with farmer’s backyard scavenging system but the yolk colour was significantly (P<0.05) superior when compared to all other treatment groups. Haugh unit score and Albumin index was significantly (P<0.05) high for scavenging fed birds compared to other groups. Shank length was not significantly (P<0.05) influenced by the treatment groups, while Shank pigmentation was significantly (P<0.05) better in scavenging group compared to other groups.